Prenatal Diagnosis, Fetal Surgery, Recurrence Risk and Differential Diagnosis of Neural Tube Defects - Chih-Ping Chen (Elsevier, 2008)
Prenatal screening with α-fetoprotein (AFP) and ultrasonography have allowed the prenatal diagnosis of neural tube defects (NTDs) in current obstetric care, and open spina bifida has been considered a potential candidate for in utero treatment in modern pediatric surgery. This article provides an overview of maternal serum AFP screening, amniotic fluid AFP assays, amniotic fluid acetylcholinesterase immunoassays and level II ultrasound for NTDs, prenatal repair of fetal myelomeningocele, recurrence risk of NTDs, and differential diagnosis of NTDs on prenatal ultrasound.